Thoracodorsal artery perforator flap in immediate breast reconstruction: a series of twenty cases - Reddy, Thyagaraj; Dikshit, Vashisht; Tilak, Balgangadhara; M. S., Ganesh (International Surgery Journal, 2019)
Background: The management of breast cancer has shown a progressive change, from radical ablative surgery, to breast conserving techniques. Traditionally, the mini latissimus dorsi flap has been used for reconstruction; which is associated with donor site morbidity. Vascular research has now allowed the use of perforator-based flaps for reconstruction, which reduce donor site morbidity. Methods: Twenty thoracodorsal perforator flaps in twenty early breast cancer patients were studied between January 2018 and December 2018. Parameters studied were adequacy of volume, ease and time taken for flap elevation, and final aesthetic outcome. Results: Flap volume was adequate to fill defect. One of twenty cases had flap loss due to venous congestion secondary to pedicle kinking. Average time taken for flap elevation was 70.45 minutes. All patients were satisfied with cosmetic outcome. Conclusions: The TDAP flap is a safe and reliable flap which provides adequate volume for partial breast reconstruction.